A Study of the Geography of 1 Enoch 17-19 : "No One Has Seen What I Have Seen" - Bautch, Coblentz, (Supplements to the Journal for the Study of Judaism ;, 2003)
A Study of the Geography of 1 Enoch 17-19 examines the travels of the patriarch Enoch who is given a guided tour of extraordinary and at times terrifying places located throughout the cosmos. Coblentz Bautch clarifies the text of 1 Enoch 17-19 by explaining how the sites described relate to one another geographically and by reconstructing the mental map of the geography that lies behind the textual descriptions. Especially provocative is the consideration of sources from the ancient Near East, Hebrew Bible and the world of Hellenistic Judaism that may have informed the world view of 1 Enoch 17-19 and parallel traditions. Through this study an important facet of apocalypses is illumined: their portrayal of geography and sacred space.